2016
DOI: 10.14254/2071-789x.2016/9-3/3
|View full text |Cite
|
Sign up to set email alerts
|

Development of Publicly Funded eHealth in Poland: Barriers and Opportunities

Abstract: eHealth is a fast growing area of health care. Its development is strongly supported by the European Commission (EC). In Poland, eHealth is connected mainly to medical information systems. Little attention is given to its clinical aspects. The paper aims at describing barriers and opportunities of public eHealth development in Poland. It is based on desk search studies and interviews conducted in Poland in the spring of 2015. An attempt to estimate size of the eHealth market was made. In the study 227 eHealth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…By doing so, the theoretical gap in the acceptance of healthcare applications by older adults has been filled. Prior studies on eHealth focussed mainly on the level of using eHealth by older adults in Poland or by the population as a whole [ 68 , 69 , 71 , 72 , 73 ]. Moreover, this study would help government carries out feasible plans to facilitate the adoption of such technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By doing so, the theoretical gap in the acceptance of healthcare applications by older adults has been filled. Prior studies on eHealth focussed mainly on the level of using eHealth by older adults in Poland or by the population as a whole [ 68 , 69 , 71 , 72 , 73 ]. Moreover, this study would help government carries out feasible plans to facilitate the adoption of such technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [ 69 ] also showed that even though eHealth is a fast-growing area of healthcare in Poland as its development is strongly supported by the European Commission (EC), it is not effectively supported by the central government and the National Health Fund (the public purchaser of health services in Poland). Another study of [ 70 ] showed that doctors were quite pessimistic when they were asked about the possible use of telemedicine among senior citizens in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, clearly, according to the medical professionals organizing and implementing an EMR is for the benefit of the health consumer and the health unit, since, it might lead to significant savings in time and costs by avoiding medical and other test redundancies. However, the governments can also benefit from such systems deployed in the public and private hospitals of their responsibility since EMR deployment everywhere has the potential of dramatically reducing the workload of the medical professionals at times when there appears to be a certain shortage of those especially in certain European but also in the GCC countries and elsewhere [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mainly, these studies were based on the representative group of the population. There is also literature on the barriers and opportunities in development of publicly funded eHealth [ 23 ] or effectiveness of tele-medical care [ 24 ]. Thus, there are no such structured studies on equity and eHealth for Poland, thus this research will allow filling in the gaps in existing literature.…”
Section: Introductionmentioning
confidence: 99%